UNLOCKING DIVIDEND POLICY: HOW PROFITABILITY AND MARKET VALUATION DRIVE PAYOUTS IN INDONESIAN STATE OWNED BANKS - Rembokowati, Ni Asa; Fadhillah, Muhammad Haris (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
This study analyzes the determinants of dividend policy in state-owned banks in Indonesia during 2019â€“2024 with the Dividend Payout Ratio (DPR) as a proxy for dividend policy and the independent variables of profitability (NPM), market valuation (PBV), leverage (DER), and earnings performance (EPS). Quarterly data were analyzed using a Fixed Effect Model (FEM) panel regression with t-test, F-test, and adjusted R-squared as model diagnostics. The results show that profitability (NPM) has a positive and significant effect on dividend policy according to signaling theory, while market valuation (PBV) has a significant negative effect, indicating that banks with high valuations tend to retain earnings. Leverage (DER) and earnings performance (EPS) do not have a significant effect, but all four variables simultaneously influence dividend policy with an adjusted RÂ² of 0.891596, reflecting the model's high explanatory power. These findings confirm the dominant role of profitability and the negative influence of market valuation in the formation of dividend policy, contributing to the literature on dividend policy in emerging markets and providing practical implications for investors, regulators, and bank management in optimal dividend strategies.